Tingkat Kepuasan Karyawan dan Perusahaan Atas Manfaat BPJS: Yufendy and Partners - Dhyana, Ayu; Dongoran, Johnson (Jurnal Maksipreneur, 2024)
Every country has its policy to make its health program for people’s welfare, including Indonesia. One of the Indonesian health programs is the Social Security Agency (BPJS). However, this research is focused specifically on the BPJS for employees and the company, which aims to be used for directing, evaluating, or improvingthe qualityof that BPJS.The type of this research is qualitative research that used primary data, where the researcher conducted indirect interviews in the form of open-ended questions to nine informants who are employees of the Yufendy and Partners Jakarta Jakarta company. The sampling technique used was a saturated sampling method, that formed as the level of satisfaction from using BPJS benefits and its determinants for Yufendy & Partners Jakarta company and its employees. The data then were analyzed using qualitative descriptive analysis techniques. The results found that the employees and company weresatisfied with the benefits of BPJS. However, it is still required further evaluation of the BPJS facilities, such as the lodgment, medicines, and other free facilities. Meanwhile, the determinants for the level of satisfactionwith BPJS benefits are communication, competence, awareness, individual, psychological, organizational, environmental, speed, coverage, economics, and responsiveness.